2017
DOI: 10.1097/mpa.0000000000000776
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Etiology, Severity, and Mortality of 3260 Patients With Acute Pancreatitis According to the Revised Atlanta Classification in Jiangxi, China Over an 8-Year Period

Abstract: Cholelithiasis was the main etiology in Jiangxi, China, and hyperlipidemia ranked second. There were different etiological proportion according to age, sex, and severity. Furthermore, the higher mortality rate occurred in severe idiopathic and hyperlipidemic pancreatitis, although there was no clear association between mortality and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
136
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 32 publications
24
136
1
Order By: Relevance
“…In a recent study on the different etiological factors of AP, 1,914 patients were considered for the causes of their AP, and this study revealed cholelithiasis to be the primary etiology, identified in 58.7% of cases. The second most common cause was idiopathic AP, identified in 543 patients (16.7%), followed by hyperlipidemia in 467 patients (14.3%) and alcohol in 148 patients (4.5%) [6]. …”
Section: Etiology Of Apmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on the different etiological factors of AP, 1,914 patients were considered for the causes of their AP, and this study revealed cholelithiasis to be the primary etiology, identified in 58.7% of cases. The second most common cause was idiopathic AP, identified in 543 patients (16.7%), followed by hyperlipidemia in 467 patients (14.3%) and alcohol in 148 patients (4.5%) [6]. …”
Section: Etiology Of Apmentioning
confidence: 99%
“…It typically causes self-limiting conditions involving the gastrointestinal and respiratory systems. Several retrospective and prospective studies in the literature have demonstrated the role of Coxsackie B virus in AP, where patients manifested symptoms of AP, and the virus was identified by immunohistochemistry methods and serologic tests (antibodies against viral antigens) [6]. Recently, different serotypes of Coxsackie virus B4, such as CB4-P and CB4-V, have been found to cause both acute and chronic pancreatitis, possibly due to different immune-mediated mechanisms [17].…”
Section: Viral Causes Of Apmentioning
confidence: 99%
“…Hypertriglyceridemia (HTG), which is one of the three most common causes of AP, occurs in 14.3% of AP patients [2]. Compared to other etiologies, patients with hyperlipidemia acute pancreatitis (HLAP) show a higher mortality rate, more severe prognoses and more frequent local complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of AP attacks are mild and resolve spontaneously with simple support, while severe local and systemic complications occur in 15–20% of cases [1, 2]. Despite progress in diagnosis and treatment, mortality in cases of severe AP is still high [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of AP attacks are mild and resolve spontaneously with simple support, while severe local and systemic complications occur in 15–20% of cases [1, 2]. Despite progress in diagnosis and treatment, mortality in cases of severe AP is still high [1, 3]. Predicting cases that may exhibit a severe course, transferal to intensive care and early aggressive treatment can reduce mortality and morbidity in these patients [4, 5].…”
Section: Introductionmentioning
confidence: 99%